Attraction and expulsion factors that affect physician migration. The Pedro Aguirre Cerda case study - Parra-Giordano, Denisse; Soto-Malabrigo, Patricia (Universidad y Salud, 2020)
Introduction: Migration is a worldwide phenomenon that affects workers from different areas, including health professionals. Objective: To determine the attraction-expulsion factors that have motivated foreign medical doctors to migrate to Chile, this study analyzed the perspective of those who are responsible for health care in the Primary Health Care model. Materials and methods: A theoretical-explanatory case study was carried out in the municipality of Pedro Aguirre Cerda (Chile), using a qualitative approach in critical epidemiology. Individual semi-structured interviews were administered to decision-making personnel in the Primary Health Care model. Results: The following were identified as attraction factors: (i) job stability of foreign physicians at the PHCs; (ii) recognition of Chile as their home; and (iii) the supply-demand relationship seen in high-rotation jobs. On the other hand, the absence of policies of inclusion and incentives for physicians working at PHCs, and differences in medical professional training abroad were characterized as expulsion factors. Conclusions: The identification of factors that influence the attraction and expulsion of medical doctors to/from Chile contributes to generating public policies that improve the working conditions of these health professionals.